Process for preparing ethylene and/or propylene and a butadiene-enriched product - VAN WESTRENEN JEROEN (2014)
The present invention provides a process for preparing ethylene and propylene and a butadiene-enriched product, comprising the steps of: a) providing a C4 hydrocarbon stream, comprising iso-olefins and butadiene. b) subjecting the C4 hydrocarbon stream to an etherification process, wherein the iso-olefins are converted with methanol and/or ethanol to an tert-alkyl ether in the presence of a catalyst, wherein the molar ratio of alcohol to iso-olefin is maintained above 1, and retrieving an etherification product stream; c) separating the etherification product stream into an ether-enriched stream and a butadiene-enriched product; d) converting the tert-alkyl ether in the ether-enriched stream to ethylene and/or propylene by contacting least part of the ether-enriched stream with a molecular sieve-comprising catalyst at a temperature in the range of from 350 to 1000° C. and retrieving an olefinic product comprising ethylene and/or propylene.